Strategi Komunikasi Pengurus BUMDes dalam Meningkatkan Partisipasi Masyarakat melalui Media Digital - Rudi Hartono; Khomsarial Romli; Ade Nur Istiani (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This research was conducted using field research. This study examines the communication strategies used by Badan Usaha Milik Desa in Pekon Tanjung Heran Village to increase community participation. The purpose of this study is to describe the communication strategies used by Badan Usaha Milik Desa in Pekon Tanjung Heran Village to increase community participation in village development programs. A descriptive qualitative research method was used in this study, utilizing data from interviews, observations, and documentation. The data from this study were analyzed using in-depth descriptive analysis and reviewed to be able to narrow down the results of the analysis properly and correctly. The results of this study found that socialization is the most effective communication strategy used by Badan Usaha Milik Desa in Pekon Tanjung Heran Village to communicate with the community. Direct socialization to the community allows Badan Usaha Milik Desa in Pekon Tanjung Heran to target all levels of society, both the older and younger generations, so that all levels of society can receive information directly from the management.